PENGGUNAAN PRINSIP-PRINSIP PERJANJIAN ISLAM DALAM PEMBUATAN AKTA NOTARIIL - Yuniar Achmad Andy Pradana Putra (International Significance of Notary, 2021)
Tujuanpenelitianini: 1) untukmengetahuipenggunaanprinsip-prinsipislamapasaja yang terdapatdalampembuatanakta   notarial, 2) Untukmengetahuikriteriaakadperjanjianislam yang      dapat            dimuatdalampembuatanaktaotentik notarial, 3) untuk mengetahui kesesuaianundang-undangjabatannotaris no 2 tahun  2014 denganprinsipakad yang adadalamhukumislamdalampembuatanaktanotariil.Penelitianinimerupakanberjenispenelitianyuridisnormatifdengansifatdeskriptif‎analitis, yaknimengkajiinformasidenganmengacu pada teorihukum yang sifatnya general kemudianditerapkangunamenjabarkanterkaitdenganbermacaminformasi lain yang berkaitan. Hasil penelitianiniAsas-asas pada hukumperjanjian Islam yang bisadiimplementasikansecaranorma pada penyusunanaktaautetikantara lain asasikhtiyariataukerelaan, asasamanahatauketepatanjanji yang sejalandenganasas pacta sunt servanda, dan asastaswiyahataukesetaraan yang searasdenganasaskeseimbangandalam Kitab Undang-Undang Hukum Perdata. Akadsebagaimanamenjadiacuandalampenyusunanaktaautentiknotariilmengacu pada Surat Al Baqarah ‎ayat 282 yang intinyabahwasanyapenyusunanseluruhakadataupunaktaautentikwajibdisaksikansetidaknyaduasaksi. Notarissepatutnyamenguasaisecaramendetilterkaitdenganperbandinganantaraasas yang terdapatdalamperjanjianmenuruthukum Islam denganasas-asasperjanjianmenuruthukumpositif di Indonesia. Kesimpulannyapenyusunanaktaautentikdapatmengacu pada prinsip-prinsipsebagaimanadiajarkandalamajaran Islam dengantetapmematuhiamanathukumpositifdalampenyusunanaktaautentik.‎ Kata kunci : Asas-AsasPerjanjian, Hukum Islam, AktaNotariil The objectives of the current study are: 1) to find out what Islamic principles are used in drafting a notarial deed, 2) to find out the criteria for Islamic agreement that can be included in drafting an authentic notarial deed, 3) to determine the suitability between the Law on Notary Position No. 2 of 2014 and the principle of the contract contained in Islamic law concerning the drafting of a notarial deed. This is a normative juridical research which is descriptive and analytical. It examines information by referring to general legal theory and then applies it to describe various other related information. According to the results of the study, the principles of Islamic contract law that can be implemented normatively in drafting authentic deeds include the principle of ikhtiyari or willingness, the principle of trustworthiness or the accuracy of promises that are in line with the principle of pacta sunt servanda, and the principle of taswiyah or equality which is in line with the principle of balance in the Civil Code. The contract, as a reference in the preparation of an authentic notarial deed, refers to Surah Al Baqarah verse 282 which explains that the preparation of all authentic contracts or deeds must be witnessed by at least two witnesses. A notary should master in detail the comparison between the principles contained in the agreement according to Islamic law and the principles of the agreement according to positive law in Indonesia. In conclusion, the preparation of an authentic deed can refer to the principles as taught in Islamic teachings while still complying with the mandate of positive law in the preparation of an authentic deed.‎Keywords : principles of agreement, Islamic law, notarial deed